Beyond Freedom and Dignity: Aleksandr Solzhenitsyn and the American Gulag - Robbins, Ira P. (1980)
A review of The Gulag Archipelago 1918-1956: An Experiment in Literary Investigation. Volume III by Aleksandr I. Solzhenitsy